Influence of Lipoprotein (a) Levels and Isoforms on Fibrinolytic Activity – Study in Families with High Lipoprotein (a) Levels - Falcó, Cristina; Estellés, Amparo; Dalmau, Jaime; España, Francisco; Aznar, Justo (Thrombosis and Haemostasis, 1998)
Increased levels of lipoprotein (a) [Lp(a)] have been considered an independent risk factor for cardiovascular disease, but the mechanism behind this relationship is not completely understood. A high concentration of Lp(a) may interfere with fibrinolysis because of the structural similarity between apo(a) and plasminogen. The aim of the present study was to examine the influence of apo(a) levels and isoforms on fibrinolytic activity in 82 subjects from 24 families in which the Lp(a) levels were ≥30 mg/dl in at least one child and one parent. Several fibrinolytic parameters, including plasmin generation by fibrin-bound tissue plasminogen activator, the lipid profile and apo(a) isoforms were studied. Subjects with high circulating Lp(a) levels (n = 44) had significantly reduced plasmin generation compared with their relatives with normal Lp(a) levels (n = 38). A significant inverse correlation between Lp(a) levels and plasmin generation was observed. The individuals with a combination of high levels of plasma Lp(a) and a major apo(a) isoform ≤580 kD molecular weight show the lowest fibrinolytic activity. A high correlation was found between the levels of apo(a) isoforms in children and the levels of the corresponding parental apo(a) iso-forms. We conclude that the antifibrinolytic effect of Lp(a) in subjects with two apo(a) isoforms may depend not only on the total plasma level of Lp(a) but also on the relative concentration of the small apo(a) isoform.